2024
DOI: 10.21273/hortsci17482-23
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Hybrid Rootstocks Improve Productivity of Tomato Grown under High-temperature Stress

Ahmed Hashem,
Yousry Bayoumi,
Abd El-Shafik El-Zawily
et al.

Abstract: Grafting can be a useful technology to improve productivity of vegetable crops, including tomato, particularly under the serious challenges of climate change for agricultural systems. This study aimed to evaluate the impact of some local tomato interspecific hybrid rootstocks along with Maxifort on the vegetative growth, productivity, and fruit quality of tomato under field production conditions. Heat-tolerant tomato hybrid 023 F1 was used as a scion over the two late summer seasons of 2021 and 2022. Grafting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This result suggests that both the Suzuka and Kaiser rootstocks were better adapted to the greenhouse microclimatic conditions and responded better to the adopted cultivation practice than Top Bental, fully expressing their productive potential. Several authors have suggested that grafting tomato plants onto vigorous rootstocks improves fruit yield [46][47][48]. An increased efficiency of nutrient and water use, as a result of more vigorous root system development [49,50], was reported to play an important role in promoting the yield of grafted plants.…”
Section: Yield-related Traitsmentioning
confidence: 99%
“…This result suggests that both the Suzuka and Kaiser rootstocks were better adapted to the greenhouse microclimatic conditions and responded better to the adopted cultivation practice than Top Bental, fully expressing their productive potential. Several authors have suggested that grafting tomato plants onto vigorous rootstocks improves fruit yield [46][47][48]. An increased efficiency of nutrient and water use, as a result of more vigorous root system development [49,50], was reported to play an important role in promoting the yield of grafted plants.…”
Section: Yield-related Traitsmentioning
confidence: 99%